Alkaline-Potassium Ferrate Pretreatment Promoting Acid Production Through Co-Fermentation of Waste Activated Sludge and Corn Straw - Xintian YU; Wei ZENG (能源环境保护)
Waste activated sludge (WAS) is a valuable waste resource rich in organic matter and nutrients, presenting significant potential for recycling. The recovery of carbon (C) and phosphorus (P) from WAS contributes to achieving carbon neutrality goals and helps alleviate the global shortage of phosphorus resources, thereby promoting sustainable agriculture. This study aimed to assess the effect of potassium ferrate (PF) on the co-fermentation system of waste activated sludge (WAS) and corn straw (CS) under alkaline conditions. Laboratory-scale sequencing batch reactors were used to investigate the impact of various PF dosages (0, 0.05, 0.20, 0.50 g/g VSSWAS) on the enhanced solubilization, hydrolysis, and formation of short-chain fatty acids (SCFAs) in the co-fermentation system. The results demonstrated that PF pretreatment effectively disrupted the structure of WAS flocs and CS, facilitating the release of organic matter from WAS cells and extracellular polymeric substances (EPS), and promoting the release of polysaccharides from CS. This effect was more pronounced at higher PF dosages (≥0.20 g/g VSSWAS). After a 24-hour pretreatment, the levels of soluble chemical oxygen demand (SCOD), soluble polysaccharides, and proteins in the 0.50 g/g VSSWAS PF dosage group increased by 11.9, 9.41, and 4.75 times, respectively, compared to the non-dosage group. The maximum accumulation of SCFAs at various PF dosages (0, 0.05, 0.20, 0.50 g/g VSSWAS) increased by 1.47, 1.92, and 2.21 times, respectively, compared to the non-dosage group, and the proportion of acetic acid, which is easily utilized by microorganisms, also increased. Microbial community analysis revealed a reduction in the Shannon index, with a notable enrichment of fermentation-related functional bacteria, including Firmicutes and Bacteroidota. Additionally, PF addition significantly enhanced the bioavailability of CS. At the genus level, acid-producing fermentative bacteria such as Macellibacteroides, Bacteroides, and Clostridium, known for utilizing polysaccharides like cellulose and hemicellulose, dominated the system, further boosting SCFAs production. Clostridium, an iron-reducing bacterium, can be selectively enriched at high concentrations of Fe(Ⅲ), further enhancing its abundance. The fermentation supernatant from PF-treated sludge had a higher SCFAs content and lower phosphorus (P) content, making it a suitable carbon source supplement for wastewater treatment plants. Additionally, the formation of vivianite was observed in the experimental groups, facilitating P recovery. When PF was added at 0.20 g/g VSSWAS, the recovery potential of SCFAs and P was optimal, and the economic benefit was the highest, reaching 63.96 CNY/m3 WAS. Therefore, a PF dosage of 0.20 g/g VSSWAS is recommended, providing a valuable reference for the resource recovery and utilization of WAS and CS. This method demonstrates significant engineering application potential and economic benefits, offering a novel approach for waste resource utilization.